Italy and the European Union: A Legal Analysis - Cananea, Giacinto della (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
The tasks of this chapter are two-fold: descriptive and interpretative. The first is to describe essential facts concerning the relationship between the Italian legal order and that of the European Economic Community, now the European Union (EU). In this respect, it is important not to lose sight of the evolving nature of European construction and the increasingly strong foundations of integration in Italian constitutional settlement. This section seeks to lay the groundwork for a later discussion of these interpretations. There are contending theories and the literature is rapidly evolving. The chapter suggests that while the acquis is hardly susceptible to being re-discussed, the emergence of political movements and parties characterised by sceptical views about European integration may impinge on the role of Italy within the EU.Keywords: integration, sovereignty, primacy of EU law, choice for Europe, counter-limits, Italian Constitution, dualism